Genome-wide identification and expression analysis of PERK genes in peanut and revelation of bidirectional immune regulatory function - Peng, Jinfeng; Liu, Wei; Yu, Jian; Fu, Danyang; Sun, Yaya; Zheng, Xiangrong; Chen, Yuanyuan; Xia, Fucai; Chen, Jiajia (Frontiers in Plant Science, 2026)
IntroductionProline-rich extensin-like receptor kinases (PERKs) represent a distinct subclass of plant receptor-like kinases (RLKs) ubiquitous in plants. While characterized in several species, a comprehensive analysis of the PERK gene family in cultivated peanut (Arachis hypogaea L.) remains limited.MethodsA genome-wide identification and systematic characterization of the PERK gene family in peanut was conducted. Evolutionary analysis was performed via phylogenetics and motif identification. Gene structures and promoter cis-elements were analyzed in silico. Expression profiles were assessed across tissues and under abiotic stresses. Functional validation of selected genes in plant innate immunity was performed.ResultsTwenty-three PERK genes (PERK1-PERK23) were identified, unevenly distributed across 12 chromosomes (highest density on chromosome 5). Phylogenetic analysis with Arabidopsis PERKs classified them into three subgroups (I-III), with Subgroup II predominantly containing peanut members. All genes contain introns and share conserved motifs. Promoter analysis revealed stress-responsive elements, including light-responsive (all genes), MeJA-responsive (18 genes), and ABA-responsive (16 genes) elements. Expression profiling showed constitutive expression for 11 genes, ubiquitous high expression of PERK6/PERK20, and root/nodule-specific expression of PERK13/PERK14. Under abiotic stress, 12, 9, and 6 genes responded to low temperature, drought, and ABA, respectively. Functionally, PERK4, PERK12, and PERK15 significantly suppressed plant innate immunity, whereas PERK8 enhanced it.DiscussionThis study provides the first genome-wide analysis of the PERK family in peanut, revealing its evolutionary features and expression patterns. Crucially, functional characterization demonstrates that peanut PERKs can bidirectionally modulate plant innate immunity, with members acting as either negative or positive regulators. This discovery of their immune regulatory functions offers novel molecular targets for stress-resistance breeding in legume crops.